Radiation therapy for de novo anorectal cancer in patients with a history of prostate radiation therapy - Hilal, Lara; Wu, Abraham J.; Reyngold, Marsha; Cuaron, John J.; Navilio, John; Romesser, Paul B.; Dreyfuss, Alexandra; Yin, Sean; Zhang, Zhigang; Bai, Xing; Berry, Sean L.; Zinovoy, Melissa; et al. (Frontiers in Oncology, 2022)
Introduction: Radiation therapy (RT) for anorectal cancer after prior prostate cancer RT is usually avoided due to concern for complications. Data on this topic is scarce. Our aim was to evaluate tolerability, toxicity, and outcomes associated with a second course of pelvic radiation in men with de novo anorectal cancers previously treated with RT for prostate cancer. Methods: We conducted a single-institution retrospective study of men treated with RT for rectal or anal cancer after prior prostate RT. Toxicity data were collected. Treatment plans were extracted to assess doses to organs at risk and target coverage. Cumulative incidence was calculated for local and distant progression. Kaplan-Meier curves were used to estimate overall survival (OS) and progression-free survival(PFS). Results: We identified 26 patients who received anorectal RT after prostate cancer RT: 17 for rectal cancer and 9 for anal cancer. None had metastatic disease. Prior prostate RT was delivered using low dose rate brachytherapy (LDR), external beam RT (EBRT), or EBRT + LDR. RT for rectal cancer was delivered most commonly using 50.4Gy/28 fractions (fr) or 1.5 Gy twice-daily to 30-45 Gy. The most used RT dose for anal cancer was 50Gy/25 fr. Median interval between prostate and anorectal RT was 12.3 years (range:0.5 - 25.3). 65% and 89% of rectal and anal cancer patients received concurrent chemotherapy, respectively. There were no reported ≥Grade 4 acute toxicities. Two patients developed fistulae; one was urinary-cutaneous after prostate LDR and 45Gy/25fr for rectal cancer, and the other was recto-vesicular after prostate LDR and 50Gy/25fr for anal cancer. In 11 patients with available dosimetry, coverage for anorectal cancers was adequate. With a median follow up of 84.4 months, 5-yr local progression and OS were 30% and 31% for rectal cancer, and 35% and 49% for anal cancer patients, respectively. Conclusion: RT for anorectal cancer after prior prostate cancer RT is feasible but should be delivered with caution since it poses a risk of fistulae and possibly bleeding, especially in patients treated with prior LDR brachytherapy. Further studies, perhaps using proton therapy and/or rectal hydrogel spacers, are needed to further decrease toxicity and improve outcomes.